Effectiveness of Intensive Case Management for Substance-Dependent Women Receiving Temporary Assistance for Needy Families - Morgenstern, Jon (© American Journal of Public Health 2006, 2006)
Objective. We tested the effectiveness of a long-term coordinated care strategy—intensive case management (ICM)—compared with usual care (UC) among a group of substance-dependent women receiving Temporary Assistance for Needy Families (TANF). Methods. Substance-dependent women on TANF (N=302) were recruited from welfare offices. They were assessed and randomly assigned to ICM or UC; follow-up was at 3, 9, and 15 months. UC consisted of a health assessment at the welfare office and a referral to substance abuse treatment and TANF services. ICM clients received ICM services in addition to UC services. Results. ICM clients had significantly higher levels of substance abuse treatment initiation, engagement, and retention compared with UC clients. In some cases, ICM treatment attendance rates were double those of UC rates. Additionally, almost twice as many ICM clients were abstinent at the 15 month follow-up compared with UC clients (P<.0025). Conclusions. ICM is a promising intervention for managing the chronic nature of substance dependence among women receiving TANF. Future research should refine long-term care strategies—such as ICM—that address the chronic nature of substance dependence among low-income populations.